Faktor risiko obesitas pada ibu rumah tangga miskin - Digna Niken Purwaningrum; Hamam Hadi; I Made Alit Gunawan (Jurnal Gizi Klinik Indonesia, 2012)
Background: Food insecurity is associated with allocation of income for high energy density food consumption that may cause obesity in poor family. In addition, low physical activity may lead to obesity, particularly in individual living in disadvantaged situation.Objective: To identify risk factors of obesity among poor housewives in Yogyakarta.Method: This was a case control study, case group was obese housewives and the control group was non obese housewives. The locations of the study were Bumijo and Pringgokusuman which have high population density. The samples were taken purposively. Each group consisted of 70 housewives (1:1) and were matched according to age. Mc.Nemar test and conditional logistic regression were used to identify the risk factors of obesity.Results: There was no difference in characteristics between the two groups. Food insecurity reached 91,43% in the control group, proportion of excessive energy intake reached 37.86% in the case group, higher than in control group (24.29%). Excessive fat intake in the case group reached 30% whereas in the control group was 28.57%. Low physical activity reached 40% in the case group, and 10% in the control group. The result of Mc.Nemar test showed that food insecurity, energy and fat intake had no significant association with obesity (p>0.05). While physical activity was associated with obesity (p=0.0001). The result of conditional logistic regression showed physical activity was dominant risk factor for obesity among poor housewives (R2=0.1916).Conclusion: Food security status was not a risk factor for obesity in poor families; energy intake and fat intake contributed to the prevalence of obesity though the influence was smaller than physical activity.